An Atkinson-Gini family of social evaluation functions: Theory and illustration using data from the Luxembourg Income Study - Abdelkrim Araar; Jean-Yves Duclos (Luxembourg Income Study (LIS), 2005)
We investigate the properties of a family of social evaluation functions and inequality indices which merge the features of the family of Atkinson (1970) and S-Gini (Donaldson and Weymark (1980, 1983), Yitzhaki (1983) and Kakwani (1980)) indices. Income inequality aversion is captured by decreasing marginal utilities, and aversion to rank inequality is captured by rank-dependent ethical weights, thus providing an ethically-flexible dual basis for the assessment of inequality and equity. We demonstrate a few of their interesting properties. We also illustrate their application using data from the Luxembourg Income Study.
Keywords: 330; Einkommensverteilung; Disparitätsmaß; Gini-Koeffizient; Altruismus; Theorie